Deskripsi Metode Modeling The Way pada Pembelajaran Bahasa Indonesia Siswa Kelas V di SD Negeri 26 Sungai Pinyuh - Muhammad Adithia Rifansyah (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This study focuses on the Description of the Modeling The Way Method in Indonesian Language Learning for Class V of SDN 26 Sungai Pinyuh, there are children who are not yet able to speak in front of the class in language learning. This is because most students still think that Indonesian is a boring subject. Then the purpose of this study is to determine the use of the Modeling The Way method and the inhibiting factors and supporting factors for the use of the Modeling The Way method in Indonesian language learning. This type of research uses descriptive qualitative research. The subjects of this study were grade V teachers and grade V students. Data collection techniques used observation techniques. While those used by this study are data collection, data reduction, data presentation, drawing conclusions. The results of this study are using the Modeling The Way learning method in the Indonesian language learning process, students are better able to understand the material given by the teacher and are more confident, able to speak in front of many people with confidence without fear of being wrong, afraid of being laughed at and students are more interested in this method, teachers also find it easier to assess each individual in the learning process towards student creativity.